THEORETICAL PRECONDITIONS FORTHE DEVELOPMENT OF ACCOUNTING IN FORESTRY ENTERPRISES ON THE CHALLENGES OF SUSTAINABLE DEVELOPMENT - Танасієва, Марина (Journal of Innovations and Sustainability, 2023)
The purpose of the article is the formation of theoretical principles of accounting in forestry enterprises on the challenges of the concept of sustainable development, in terms of defining the directions of improving the information support system of rational forestry for the purpose of preservation, reproduction and use of forest resources at the micro and macro levels of the economy.
Keywords: сталий розвиток; розвиток бухгалтерського обліку; лісове господарство